2018
DOI: 10.1039/c8ta05282d
|View full text |Cite
|
Sign up to set email alerts
|

Metallic tin substitution of organic lead perovskite films for efficient solar cells

Abstract: Low-leaded perovskite solar cells are operated using inorganic active metal substitution of lesser active organometal halide perovskite.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 59 publications
0
14
0
1
Order By: Relevance
“…The Sn 5p induced electronic states are highly delocalized in nature and are likely to lower the effective mass and improve the mobility and exciton diffusion lengths of holes which is beneficial for charge separation. Nevertheless, a more careful band structure calculations may still be required to maximize this unique effect because by realizing MASn 0.15 Pb 0.85 I 3 mixed metal perovskite, Zhao et al has argued a maximum amount of 15% Sn content to be the optimum addition into the perovskite lattice for improved performance . Optical measurements also revealed that substituting Pb ions for Sn ions up to 80 wt% Sn content reduces the bandgap of perovskite films.…”
Section: Photophysical Properties Of Sn Halide Perovskitesmentioning
confidence: 99%
“…The Sn 5p induced electronic states are highly delocalized in nature and are likely to lower the effective mass and improve the mobility and exciton diffusion lengths of holes which is beneficial for charge separation. Nevertheless, a more careful band structure calculations may still be required to maximize this unique effect because by realizing MASn 0.15 Pb 0.85 I 3 mixed metal perovskite, Zhao et al has argued a maximum amount of 15% Sn content to be the optimum addition into the perovskite lattice for improved performance . Optical measurements also revealed that substituting Pb ions for Sn ions up to 80 wt% Sn content reduces the bandgap of perovskite films.…”
Section: Photophysical Properties Of Sn Halide Perovskitesmentioning
confidence: 99%
“…The crystal growth rate of tin halide perovskites can also be modulated by other interactions such as hydrogen bonds, hydrophilic‐hydrophobic self‐aggregation, intermolecular forces, and halide bonding. [ 7,37–39,141–147 ] For example, Meng et al. introduced hydrogen bonding interactions into tin halide perovskite by adding poly(vinyl alcohol) (PVA) into precursor solution ( Figure 11 a).…”
Section: Crystallization Modulationmentioning
confidence: 99%
“…The crystal growth rate of tin halide perovskites can also be modulated by other interactions such as hydrogen bonds, hydrophilic-hydrophobic self-aggregation, intermolecular forces, and halide bonding. [7,[37][38][39][141][142][143][144][145][146][147] For example, Meng et al introduced hydrogen bonding interactions into tin halide perovskite by adding poly(vinyl alcohol) (PVA) into precursor solution (Figure 11a). The hydrogen bonding interactions between hydroxyl group and iodide ion could not only retard the crystal growth to form dense and uniform films, but also suppress iodide ion migration on the grain boundary, which benefited the long-term stability for tin halide perovskite devices and obtained a PCE up to 8.9%.…”
Section: Other Additivesmentioning
confidence: 99%
“…The partial addition of Sn into the conventional perovskites (to form HPVKs) provided synergetic advantages: 1) stabilization of the Sn in its bivalent state, 2) reduction in the overall toxicity of the compound, and 3) bandgap tunability toward the ideal one. [ 93 ] For example, Ogomi et al [93b] partially substituted Pb with Sn for the first time and prepared several less toxic HPVKs (MASn x Pb (1− x ) I 3 ) with tunable bandgap (1.5–1.1 eV) (see Figure a,b). Due to the reduced bandgap, the optimized HPVK (MASn 0.5 Pb 0.5 I 3 ) demonstrated a redshift of 253 nm in the incident photon‐to‐electron conversion efficiency (IPCE) curve edge and reached as high as 1060 nm (see Figure 10c).…”
Section: Hpvksmentioning
confidence: 99%